NUTRITIONAL STATUS, DIETARY PRACTICES, AND NUTRITION KNOWLEDGE OF SCHOOLCHILDREN - Costa, Mayara Carvalho; de Sousa, Artemizia Francisca; Lima, Jarlan Ted do Nascimento; de Sousa, Sabrina Delany Frota; Ferreira, Francisco Valdicélio; Marques, Aline Rocha de Azevedo (Journal of Health Care, 2018)
Introduction: The increase in the number of cases of childhood obesity is progressively more frequent in several countries, including Brazil, what is closely related to lifestyle changes and poor eating habits. Objective: To evaluate the nutritional status, eating habits, and nutrition knowledge of schoolchildren from 8 to 10 years of age, in a private school in the city of Picos, PI. Methodology: Cross-sectional study conducted with 49 students from 8 to 10 years old enrolled in a private school in the city of Picos. Anthropometric measurements were collected for assessment of nutritional status using as an indicator the Body Mass Index for age, classified according to the World Health Organization. For characterizing the dietary practices and determining the nutrition knowledge of the schoolchildren, we used standardized self-application questionnaires. Results: Among the 49 schoolchildren evaluated, 73.5% were eutrophic, 59.2% had good dietary practices, and 57.1% presented good nutrition knowledge. Nutritional status was significantly associated with feeding practices, with a higher occurrence of eutrophic students with good eating habits. Eutrophic students, in addition to good eating habits, had good nutrition knowledge. Conclusion: The results indicate the need for intervention strategies beyond promoting nutrition knowledge; it is also important to seek the adoption of a healthy diet and lifestyle since childhood, aimed at health promotion and prevention of diseases associated with excessive weight.
Keywords: Nutrition; anthropometry; nutritional status; school feeding